Lipase mediated synthesis of sugar fatty acid esters - Gumel, A.M.; Annuar, M.S.M.; Heidelberg, T.; Chisti, Y. (Elsevier, 2011)
This review is concerned with lipase catalyzed synthesis of sugar fatty acid esters in water immiscible organic solvents. Sugar esters are widely used nonionic and nontoxic biosurfactants. Certain sugar esters inhibit microbial growth and have other activities. Lipase mediated synthesis has important advantages over conventional chemical synthesis of sugar esters. Lipase catalyzed synthesis is typically carried out in organic solvents having a low water activity to drive the reaction towards synthesis instead of towards ester hydrolysis. The impact of the various reaction conditions on enzymatic synthesis of sugar esters in nonaqueous media is discussed. Considered in particular are the solvent effects; the effects of water activity; the influence of the nature and concentration of the reactants (sugars and fatty acids); the influence of temperature; and the effects associated with the specific nature of the lipase catalyst used.